Analyse de l’enseignement en architecture de paysage à travers la recherche sur l’évolution de la profession d’architecte-paysagiste en Lituanie - Vaiva Deveikienė (Projets de Paysage)
The article studies the history and development of training in landscape architecture in Lithuania. The development of the profession and the training of landscape architects is as complex as the history of the country. The profession had its origins in the art of gardens and parks and evolved in response to the challenges of the times and academic opportunities. At the end of the 17th century, the ancient University of Vilnius created chairs and studies in the fields of the fine arts and natural sciences and published works establishing the foundations of the profession in garden arts. In the 20th century, between the two world wars, architects, town planners and landscape architects trained in French schools. The chair of architecture was introduced at the University of Kaunas in 1940 and developed its activity during the Second World War and the Soviet post-war period. The disciplines of urban planning and landscape architecture were included in the curricula. During the Soviet period, the reorganisation of schools of higher learning enabled their development, but it was not until 1972 that a programme with a specialisation in landscape architecture was started at the Vilnius Academy of Fine Arts. After the Soviet period, in the 1990s, landscape architects taught disciplines relating to the landscape and landscape architecture at different schools such as the Academy of Fine Arts, Klaipėda University (KU), Vilnius Technical University (VGTU), Kaunas Technological University (KTU), and the Academy of Agriculture of Vytautas Magnus University. All these universities contributed to the training of landscape architects but had no programmes recognised by IFLA Europe or ECLAS. The need to create a modern curriculum has led to the emergence of two Erasmus+ projects to establish a Bachelor’s and Master’s degree in landscape architecture at Vilnius Technical University. The article presents the challenges of creating this programme of landscape architecture and the importance of international academic cooperation in this process.